(untitled) (Research, Society and Development, 2024)
Objective: The objective of this narrative literature review article is to address ozone and its antimicrobial potential, which is used in ozone therapy to treat various pathogens that affect oral health, talking about which treatments we can use this therapy in, discussing its effectiveness and mechanism of action. Methodology: Research was carried out with the aim of obtaining the maximum amount of information on the subject, so that the article would become rich, with a scientific basis and current, thus, searches were made on the following websites: DeCs, Web of Science, Science Direct, The Cochrane Library, Scielo, PUBMED Central, BVS/BIREME, Research, society and development journal and Google Academy. Results: Ozone therapy has great potential to destroy viruses, bacteria, fungi and protozoa, thus being a therapy that has an effect against pathogens that invade the human body and harm health. Conclusion: Ozone is a substance with a strong antimicrobial effect, and is widely used in dentistry, as it is effective against pathogens that cause problems in the oral cavity. It can be used in treatments against fungi, periodontal diseases, cavities, proliferation and development of dental biofilm, peri-implant mucositis and in the disinfection of root canals. Thus, ozone therapy is a therapy that has great benefits when used by dentists, increasing the range of treatments that the dentist can perform and improving the patient’s health.